Reimagining Wiretapping: Ensuring Fairness in the Law Enforcement Process - Mahdy, Mohamad; Hartiwiningsih, Hartiwiningsih; Isharyanto, Isharyanto (International Conference on Law, Technology, Spirituality and Society (ICOLESS); Vol 5 (2025): The 8th International Conference on Law, Technology, Spirituality and Society (ICOLESS), 2025)
Wiretapping plays a crucial role in the detection of criminal activities such as corruption, terrorism, and drug trafficking. However, inconsistencies and the absence of comprehensive norms in wiretapping regulations in Indonesia present significant legal challenges. The ambiguity surrounding the legitimacy of authority granted to law enforcement agencies creates the potential for abuse of power and infringes upon citizens' privacy rights. Additionally, legal uncertainties regarding the admissibility of evidence obtained through wiretapping can undermine the integrity of the criminal justice process. This study aims to develop a model for wiretapping regulations that ensures fairness in the law enforcement process. The research employs a doctrinal approach, utilizing both statutory and conceptual analysis. The findings suggest that a well-defined legal framework is essential to ensure wiretapping is conducted in accordance with legal standards and the principle of due process. Furthermore, a robust system of checks and balances must be established to prevent the abuse of authority, through clear limitations on the scope of wiretapping powers.